Adenovirus-Associated Virus Multiplication IX. Extent of Transcription of the Viral Genome In Vivo - Carter, Barrie J. (1972)
Nucleic acid hybridization procedures were used to measure the extent of transcription of adenovirus-associated virus (AAV) deoxyribonucleic acid (DNA) in KB cells in the presence of either adenovirus or herpes simplex virus as the helper. Annealing of AAV ribonucleic acid to AAV DNA was monitored by a hybridization inhibition assay on nitrocellulose filters or by hydroxyapatite chromatography. These experiments confirmed the previous observation that, in the presence of either type of helper virus, only one strand of AAV DNA (the thymidine-rich or “minus” strand) is transcribed in vivo. However, it was found that only 70 to 80% of this strand appears to be transcribed in vivo. Furthermore, studies with minus strands employing hydroxyapatite chromatography and nuclease S(1), which specifically degrades single-stranded DNA, indicated that up to 20% of the minus strand is self-complementary. It seems likely that these self-complementary sequences account for the bulk of that portion of the minus strand (20 to 30%) which is not transcribed in vivo.